Pengaruh Model Team Game Tournament terhadap Hasil Belajar Matematika Siswa Kelas VII SMPN 3 Bontang pada Materi Bilangan Rasional - Zulfahmi, Qolbiraini Azzahra; Berahman Berahman (Lembaga Pengembangan Kinerja Dosen, 2025)
The mathematics learning outcomes of students at SMP Negeri 3 Bontang on Rational Numbers are still relatively low. Data from the 2019 National Examination (UN) shows an average math score of 46.43, which is in the